Analysis of pathogens and risk factors of secondary pulmonary infection in patients with COVID-19. (July 2021) - Tang, Haicheng; Zhao, Zhangyan; Zhang, Xiaolin; Pan, Lei; Wu, Qingguo; Wang, Mei; Zhang, Yunbin; Li, Feng
Abstract: To investigate the distribution and risk factors of pathogens in secondary pulmonary infection in patients with COVID-19.142 patients with confirmed COVID-19 from Shanghai Public Health Clinical Center were collected, and 32 patients with pulmonary infection were taken as the infection group. The distribution of pathogens in the sputum specimens was applied for retrospective analysis. Meanwhile, 110 patients diagnosed with COVID-19, but without pulmonary infection were regarded as the asymptomatic group. The risk factors of pulmonary infection were analyzed with generalized linear models and logistic regression. The pathogens in the lung infection group were mainly gram-negative bacteria (22, 68.8%), especially Klebsiella pneumoniae . Gram-positive bacteria and fungi accounted for 13 (40.6%), mainly Staphylococcus aureus, and 11 (34.4%), mainly Candida albicans . There were 14 cases (43.8%) infected with two or more pathogens. The comparison between the two groups found that, patients with elder age, underlying diseases, more lung lesions and low protein contents, were more likely to develop lung infections. At last, univariate analysis showed that 6 factors, including indwelling gastric catheter, the number of deep vein catheters, tracheal intubation tracheotomy, invasive mechanical ventilation, hormonal application, and the use of more than three antibacterial drugs, are risk factors for COVID-19 secondary pulmonary infection. Generalized linear models and logistic regression analysis showed antimicrobial use as an independent risk factor for COVID-19 secondary lung infection. There are many risk factors for secondary lung infection in severe COVID-19 patients, and it is recommended to use antibiotics reasonably. Highlights: The pathogens in the lung infection group were mainly gram-negative bacteria (22, 68.8%), especially Klebsiella pneumoniae . Patients with elder, underlying diseases, more lung lesions, low protein contents, were more likely to develop lung infections. Gastric catheter, mechanical ventilation, antibacterial drugs, et al are risk factors for COVID-19 secondary pulmonary infection. Antimicrobial use as an independent risk factor for COVID-19 secondary lung infection.